Wheels Within Wheels: The Analysis of a Cultural Event - Court, Deborah (Alberta Journal of Educational Research, 2001)
This article describes a one-semester course on qualitative research methods presented for faculty members in a university school of education. The course was one significant "cultural event" in an ongoing change process toward the inclusion of qualitative methods in a strongly positivistic setting. The inclusion of qualitative methods required a profound adjustment by participants in this culture. The change was eased by official sanction of the course and by faculty members' ability to find entry points to the ideas through established patterns of communication with the course presenters, most of whom came from within the faculty. The author is new to both the university and the country, and her own cultural adjustments, together with her role as one of the course presenters, leads her to reflect anew on the transaction between subjective and objective in qualitative research.